Multilayer bandpass filter in dual-band applications / Farhanna Razali - Razali, Farhanna (2014)
A multilayer filter technique is proposed to enhance an existing design of a dual-mode dual-band bandpass filter topology. In this paper the design adapts vias to connect two quarter-wavelength parallel coupled-lines to two half-wavelength lines creating a dual-path structure. The influence of different impedance parameters such as line impedance, Zr and even- and odd-mode impedances, Zoe and Zoo of the filter topology were analysed, thus showing the control parameters of the dual-band response in terms of the bandwidth and separation between the passbands. The adaptation of multilayer technology in this topology, improves the rejection-band of the dual-band frequency response. The multilayer filter was designed using microstrip technology at 2 GHz using Flame Retardancies 4 (FR4) material. The result shows the filter is suitable in addressing wide band applications and the concept is validated through measurement.